Pengelolaan Sampah Berbasis Komunitas: Menuju Desa Hijau dan Ekonomi Sirkular Desa Jayapura, Kabupaten Tasikmalaya - R Arif Malik Ramadhan; Hilman Anwari; Ahmad Syukur; Rizal Maulana Yusuf; Ulpah Indriana Yusup; Hani Lestari; Syahrul Nurohman; Rafi Haekal Akbar (Universitas Perjuangan Tasikmalaya, 2026)
Household waste management in rural areas remains challenging due to limited facilities, inadequate education, and the absence of source-separation habits. This community engagement program was implemented in Jayapura Village, Cigalontang Sub-district, Tasikmalaya Regency, to develop a participatory waste management system through education, provision of organic–inorganic waste bins, sorting training, and establishment of a waste bank. The program included initial observation, 3R (Reduce, Reuse, Recycle) socialization, technical training, and installation of educational media on waste decomposition times. Conducted over 35 days, the program actively involved local residents. The results indicated significant improvement in community knowledge, attitudes, and practices toward waste management. Residents began sorting waste, processing organic waste into compost and liquid fertilizer, and utilizing the waste bank to manage recyclable inorganic materials. The provision of facilities and direct mentoring fostered sustainable environmental behavior. The program also contributed to household food security and promoted village-scale circular economy practices. This model demonstrates strong potential for replication in other rural areas to achieve cleaner, healthier, and more sustainable environments.